2006
DOI: 10.1038/sj.onc.1210142
|View full text |Cite
|
Sign up to set email alerts
|

PBK/TOPK promotes tumour cell proliferation through p38 MAPK activity and regulation of the DNA damage response

Abstract: The contribution of the insulin-like growth-factor-I receptor (IGF-IR) to tumour progression is well documented. To identify new mediators of IGF-IR function in cancer, we recently isolated genes differentially expressed in cells overexpressing the IGF-IR. Among these was the serine/threonine kinase PBK/TOPK (PDZ-binding kinase/T-LAK cell-originated protein kinase), previously associated with highly proliferative cells and tissues. Here, we show that PBK is expressed at high levels in tumour cell lines compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 48 publications
11
152
1
2
Order By: Relevance
“…Our findings also agree with previous studies showing that reduced PBK expression in MCF-7 breast cancer cells led to slower growth and reduced clonogenicity in soft agar assays (Ayllo´n and O'Connor, 2007). These investigators also showed that MCF-7 tumor cells with knocked down PBK expression exhibited decreased survival following DNA damage from UV or chemotherapeutic agents as well as impaired generation of phosphorylated H2AX (g-H2AX), an early response to double-strand DNA breaks (Ayllo´n and O'Connor, 2007). Other investigators showed that knocked down expression of PBK in HCT116 colorectal carcinoma cells decreased tumorigenicity .…”
Section: Hct116-rs Hct116-shpbk1supporting
confidence: 93%
See 3 more Smart Citations
“…Our findings also agree with previous studies showing that reduced PBK expression in MCF-7 breast cancer cells led to slower growth and reduced clonogenicity in soft agar assays (Ayllo´n and O'Connor, 2007). These investigators also showed that MCF-7 tumor cells with knocked down PBK expression exhibited decreased survival following DNA damage from UV or chemotherapeutic agents as well as impaired generation of phosphorylated H2AX (g-H2AX), an early response to double-strand DNA breaks (Ayllo´n and O'Connor, 2007). Other investigators showed that knocked down expression of PBK in HCT116 colorectal carcinoma cells decreased tumorigenicity .…”
Section: Hct116-rs Hct116-shpbk1supporting
confidence: 93%
“…Cellcycle-specific regulation of PBK/TOPK is mediated partly by transcription factors E2F and CREB/ATF (Nandi and Rapoport, 2006). Previous studies also suggest a role for PBK/TOPK in cytokinesis and DNA damage sensing and repair through phosphorylation of histone H2AX (Matsumoto et al, 2004;Zykova et al, 2006;Ayllo´n and O'Connor, 2007).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Adhesion, migration, soft agar and proliferation assays These assays were conducted as previously described (Ayllon and O'Connor, 2007) with the following modifications. For adhesion assays, 1 Â 10 4 cells per well were added to previously coated wells (with fibronectin) in triplicate and allowed to attach for 30 min.…”
Section: Rt-pcr and Real-time Pcrmentioning
confidence: 99%